Implementasi Kurikulum 2013 dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah (MI) NW Tanak Mira Wanasaba - Zakaki, Zakaki (Lembaga Yasin AlSys, 2022)
The 2013 curriculum is one of the important components in education which in its implementation must be carried out and functioned as optimally as possible in accordance with their respective roles including learning Arabic in the 2013 curriculum which is part of Islamic religious education and also the language of the Qur'an which was revealed in Arabic form. The purpose of this research is to examine more deeply the problems of implementing the 2013 curriculum in learning Arabic, especially at Madrasah Ibtidaiyah (MI) NW Tanak Mira Wanasaba. The research method used is qualitative research. Data collection techniques in this study were carried out by observation, interviews and documentation in which data analysis was carried out by means of data reduction, data display and data conclusion. To obtain the validity of the data is done by means of the level of trust (credibility), transferability (transferability), the level of dependability (dependability) and trust testing. The results of the research conducted show that the implementation of the 2013 curriculum in learning Arabic, especially at Madrasah Ibtidaiyah (MI) NW Tanak Mira Wanasaba is carried out with student-centered, interactive learning activities. starting with muhadatsah in each lesson, using a network environment. is actively investigating, uses real-world contexts, empowers the rules of attachment, uses stimulation in all directions, is cooperative, is multi-conscious in nature, learning activities towards multidisciplinary knowledge and is autonomous and trustful and learning is critical and from imparting knowledge to knowledge exchange including syllabus development, class-based testing system development, life skill integration into syllabus and learning model modification.